BROADBAND MICROWAVE MEASUREMENTS OF RELATIVE PERMITTIVITY AND PERMEABILITY OF MATERIALS - Rybin, Oleg; Abbas, Tahir (Journal of Research (Science), 2025)
measuring complex permittivity and permeability of materials atbroadband microwave frequencies has been presented. Classification oftype of the measurement methods to extract the complex permittivityand permeability of bulk materials has been done in this paper.Mathematical models of all the above-mentioned measurement types ofmethods are reviewed. Advantages and disadvantages of existingmeasurement devices/systems are described according to theclassification made. A new design of test devices for the measurementsystem operating in broadband microwave frequency range has beenproposed. Measurement system on the basis of the proposed devicecan be used for a measuring the ordinary bulk materials, ferrites(including fully magnetized) and magnetic materials but much cheaperthen one to be made. The system is much cheaper than a free spacemeasurement system. The approach to define the permeability tensor ofmagnetic materials using the test device is proposed as well.